A new, spectacular, long-caudate species of Pleurothallis (Orchidaceae) from central Peru related to P. sijmii - Ocupa-Horna, Luis; Valenzuela, Luis; Ward, Raven; Wilson, Mark (Phytotaxa, 2025)
In Peru, despite being recognized for its rich diversity of orchid species, the richness of Pleurothallis species is still unknown. Here we describe and illustrate a new species of Pleurothallis found in central Peru. Pleurothallis yanesha can be easily recognized by its raceme of long caudate flowers. The new species is most similar to P. sijmii, but differs from it in the flowers with apically connivent sepals (versus partially extended), longer sepals, narrowly ovate, much longer petals, the lip smaller and without callus, with the median lobe narrowly triangular, acute, and the column strongly arched. P. yanesha is known from montane forests located within the Oxapampa-Asháninka-Yánesha Biosphere Reserve (BIOAY) in the department of Pasco. In addition, we report the first confirmed wild population of P. sijmii, and include an update of this description, taxonomic comments on the allied species and the implications of floral morphology for the pollination of these species.